2018
DOI: 10.1542/peds.2017-2888
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Young Children Born to HIV-Infected Mothers: A Meta-analysis

Abstract: Both HIV+ and HEU children had worse developmental outcomes compared with HUU children. HIV+ and HEU children with ARV exposure also had worse developmental outcomes compared with those without exposure; however, these results should be interpreted with caution. More research is needed to identify the impact of ARV exposure on young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 36 publications
(33 reference statements)
10
108
2
Order By: Relevance
“…By contrast, low maternal CD4 count did not increase the IRRs of having caries in primary teeth for the HEU children investigated in this study. This study's results are at odds with those of some previous studies , but in accordance with others . The absence of an effect of maternal CD4 count on caries might be explained by the particular characteristics of the HEU children investigated, being born to mothers who did not qualify for ARV therapy during pregnancy because of less‐advanced infection and high immune competency (i.e., CD4 count > 350 µ l −1 ).…”
Section: Discussionsupporting
confidence: 52%
“…By contrast, low maternal CD4 count did not increase the IRRs of having caries in primary teeth for the HEU children investigated in this study. This study's results are at odds with those of some previous studies , but in accordance with others . The absence of an effect of maternal CD4 count on caries might be explained by the particular characteristics of the HEU children investigated, being born to mothers who did not qualify for ARV therapy during pregnancy because of less‐advanced infection and high immune competency (i.e., CD4 count > 350 µ l −1 ).…”
Section: Discussionsupporting
confidence: 52%
“…Earlier studies revealed variable rates of GDI among PHIV children. A recent meta‐analysis of neurodevelopment in PHIV and PHEU young children reported developmental impairment (−2 SD below the mean on the Bayley Scales of Infant Development) among 21% to 35% of children; however, most of these studies did not indicate onset of ART . Our study revealed that 32% of PHIV children had developmental impairment overall, yet impairment was significantly less likely among children with early initiation of ART (22%) compared to those with later initiation of ART PHIV (44%).…”
Section: Discussioncontrasting
confidence: 50%
“…For both zidovudine‐ and lamuvidine‐exposed rodents, some studies suggested that memory and learning may be impaired at early ages . More recent clinical studies with newer ART regimens have not found such deficits in young children . Fewer data are available about specific cognitive functions in older HEU children and adolescents, but studies have found a higher frequency of reading and math impairments in HEU children compared to the general population .…”
Section: Discussionmentioning
confidence: 99%
“…For the 1.4 million children born annually to mothers living with HIV, there are concerns that HIV or antiretroviral therapy (ART) exposure may negatively impact neurodevelopment, including cognition, language and motor skills . A meta‐analysis on neurodevelopment in HIV‐exposed uninfected (HEU) children highlighted the limitations in the current body of literature including the heterogeneity of the patient populations between studies, limited confounders measured and variability in ART regimens.…”
Section: Introductionmentioning
confidence: 99%